A Demographic Characteristics-Based Study on the Visual Impact Assessment of the External Form of Entrance Pavilions to the Underground Stations of China’s Subway - Guanjun Li; Chenping Han; Jiamin Shen; Xinyu Wang; Tao Gu; Zhongju Yang; Lin Zhang (Applied Sciences, 2023)
The subway is one of urban residents’ main means of public transportation. The design of entrance pavilions to subway stations has shown a diverse development trend over time. Since most of the subway building space is underground, it is very difficult for subway users or the public to view the structure fully. In this instance, the ground-level entrance pavilion becomes the most eye-catching element in the subway system. From the perspective of the urban spatial environment, the external form of entrance pavilions is one of the components of urban architecture. The design of the external form of entrance pavilions has an important impact on the urban spatial form and affects people’s feelings about the urban space. Therefore, it is essential to study the external form of entrance pavilions. This study investigated 42 subway entrance pavilions in 17 cities in China. The following features were studied: exterior contour, façade permeability, cultural characteristics, decorative materials, and the number of exterior colors. The photostimulation method was adopted to evaluate the influence of the physical features of the external form of the entrance pavilions on respondents’ visual impact assessment. The data analysis showed that respondents with different demographic characteristics provided different visual impact assessments of the external form of the entrance pavilions, and all five physical features influenced their assessment. This study offers a valuable reference for constructing entrance pavilions and urban spaces in Chinese cities in the future.